2015
DOI: 10.1589/jpts.27.3631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tongue strength training using the Iowa Oral Performance Instrument in stroke patients with dysphagia

Abstract: [Purpose] The aim of this study was to evaluate the effectiveness of a structured program of resistance training for the tongue in order to improve swallowing function in stroke patients with dysphagia. [Subjects and Methods] Twenty-seven stroke patients with dysphagia were randomly divided into two groups. The experimental group participated in a resistance-training program involving a 1-repetition maximum, with an intensity of 80%, along with 50 repetitions per day each for the anterior and posterior regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 13 publications
4
81
0
10
Order By: Relevance
“…According to the results of the investigation on the effect of orofacial myofunctional exercise on the improvement of orofacial muscle strength and alternating motion rate in dysphagia patients, tongue elevation, tongue protrusion, cheek compression, lip compression, and alternating motion rate were significantly improved. This corresponds with the results of preceding studies that indicated that orofacial muscle exercise improved swallowing functions of stroke patients by reinforcing orofacial muscle strength and formation of oral pressure7, 8 ) .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to the results of the investigation on the effect of orofacial myofunctional exercise on the improvement of orofacial muscle strength and alternating motion rate in dysphagia patients, tongue elevation, tongue protrusion, cheek compression, lip compression, and alternating motion rate were significantly improved. This corresponds with the results of preceding studies that indicated that orofacial muscle exercise improved swallowing functions of stroke patients by reinforcing orofacial muscle strength and formation of oral pressure7, 8 ) .…”
Section: Discussionsupporting
confidence: 90%
“…For orofacial muscle strength, tongue elevation, tongue protrusion, cheek compression, and lip compression7 ) were measured by using the Iowa Oral Performance Instrument (IOPI)10 ) , which is composed of a tongue bulb and a connecting tube. The measurement methods were as follows: For tongue elevation, the bulb was placed in the hard palate of the subject, who was instructed to compress the bulb with tongue as strongly as possible for 2–3 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Videofluoroscopy Dysphagia Scale (VDS) was used to quantify the functional recovery of swallowing. VDS is a functional evaluation scale that comprehensively reflects the overall swallowing function in stroke patients7, 8 ) . In this study, 7 subtests of oral stage function were analyzed such as lip closure, bolus formation, mastication, apraxia, tongue to palate contact, premature bolus loss, and oral transit time.…”
Section: Methodsmentioning
confidence: 99%